Measurement of Residual Breast Cancer Burden after Neoadjuvant Chemotherapy - Syedah Sana Iqbal Ahmed, Asma Amin, Waqas Rind, Sumayah Khan, Rabia Masroor Hashmi (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of residual cancer burden after neoadjuvant chemotherapy for breast cancer patients undergoing surgery. Study Design: Descriptive study. Place and Duration of Study: Department of Surgery, Dr. Ruth K.M. Pfau Civil Hospital Karachi from 8th May 2019 to 7th November 2019. Methodology: One hundred and twenty six females aged 25 to 75 years with stage IIA, IIB and IIIA were enrolled. Patients who had received standard protocol of neoadjuvant chemotherapy from outside i.e. six cycles of fluorouracil, anthracycline and cyclophosphomide (FAC) every 3 weeks and for HER2+ tumors, FAC was followed by 12 cycles of Trastuzumab every 3 weeks were included. Data regarding tumor characteristic, age, HER 2 status, PR status, KI 67status and nodal involvement was noted. Results: The mean age was 47.32±13 years and mean cancer cellularity was 14.88±10.4%. Nuclear grade III was present in 39.7% patients and 48.4% patients belonged to T1 stage. Majority of patients were menopausal. FAC regime was used in 58.7% patients. RCB I (minimal residual disease) was present in 12.7% patients, RCB II (moderate residual disease) was present in 51.6% patients and RCB III (extensive residual disease) was found in 35.7% patients. Cross tabulation for age, T stage, pathological AJCC classification, histological classification and nuclear grading was not significant (p>0.05). Conclusion: Neoadjunctive therapy is associated with decrease rate of residual cancer burden. Keywords: Breast carcinoma. Neo adjunctive therapy, Decreases residual cancer burden